2021
DOI: 10.3390/diseases9040089
|View full text |Cite
|
Sign up to set email alerts
|

Cutting out Cholecystectomy on Index Hospitalization Leads to Increased Readmission Rates, Morbidity, Mortality and Cost

Abstract: Biliary tract diseases that are not adequately treated on index hospitalization are linked to worse outcomes, including high readmission rates. Delays in care for conditions such as choledocholithiasis, gallstone pancreatitis, and cholecystitis often occur due to multiple reasons, and this delay is under-appreciated as a source of morbidity and mortality. Our study is based on the latest Nationwide Readmissions Database review and evaluated the effects of postponing definitive management to a subsequent visit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Analysis of index hospitalizations' outcomes showed that the cholecystectomy group had the lowest mortality rates among the four groups. Previous studies showed that cholecystectomy was associated with decreased mortality in patients with BAP [10,54]. Both procedures group had also a comparable low mortality rate, and this was consistent with the available evidence of no additional mortality benefit when ERCP was performed along with cholecystectomy as discussed above.…”
Section: Discussionsupporting
confidence: 86%
“…Analysis of index hospitalizations' outcomes showed that the cholecystectomy group had the lowest mortality rates among the four groups. Previous studies showed that cholecystectomy was associated with decreased mortality in patients with BAP [10,54]. Both procedures group had also a comparable low mortality rate, and this was consistent with the available evidence of no additional mortality benefit when ERCP was performed along with cholecystectomy as discussed above.…”
Section: Discussionsupporting
confidence: 86%
“…Despite current recommendations, pediatric index cholecystectomy was only performed in 59% of admissions for biliary acute pancreatitis and choledocholithiasis. Interestingly, this trend is mirrored in multiple analogous retrospective studies in the adult literature, even after the foundational randomized controlled PONCHO trial, which showed that compared with delayed cholecystectomy, index admission cholecystectomy reduced rate of recurrent gallstone-related complications in patients with mild BAP [ 6 8 , 18 ]. These findings were momentous in adult literature and emphasized the needless hospital readmission and healthcare utilization brought on by delayed cholecystectomy.…”
Section: Discussionmentioning
confidence: 96%
“…The benefits of early cholecystectomy for biliary acute pancreatitis (BAP) and choledocholithiasis have been well established and include lower readmission, lower hospital length of stay, and less biliary-related complications [ 6 8 ]. However, recommendations for management of pediatric gallstone disease is largely based on small population studies, single center studies, or expert opinion [ 9 11 ].…”
mentioning
confidence: 99%
“…Children most at risk for acute cholecystitis are those with comorbid conditions that would increase their propensity to form gallstones such as hemolytic disorders, obesity, congenital malformations, parenteral nutrition, cystic fibrosis, and short bowel syndrome [ 1 , 4 ]. Early cholecystectomy in adult patients with acute cholecystitis has been widely studied and shown to be safe with less morbidity, shorter hospital stays, and lower readmission rates than those who underwent delayed cholecystectomy [ 5 – 9 ]. In contrast, ideal surgical timing and management of the pediatric population has been less studied, which has led to heterogenous management practices [ 10 ].…”
mentioning
confidence: 99%